Recent Doctoral Dissertation Research in Reading, Supplement 1. ERIC CRIER Reading Review Series, Volume 2, Bibliography 14 - Summers, Edward G., Comp.; ERIC Clearinghouse on Reading, English, and Communication ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
A listing of 344 dissertations completed in colleges and universities since 1966 in the areas of preschool, elementary, secondary, college, and adult reading is reported. Volumes 27 and 28 of "Dissertation Abstracts" were reviewed, and dissertations on reading were noted. A comprehensive, analytical abstract was prepared by professionals in reading who worked from the summary reported for each dissertation. As much as possible of the procedures, design, and conclusions of each investigation was included in the abstract. Each entry includes complete bibliographic data and information for ordering copies. Copies of any dissertation listed in the bibliography may be ordered from University Microfilms, Ann Arbor, Michigan, in positive microfilm or bound xerographic form. (CM)
Educational level discussed: Preschool Education.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Programs; Colleges; Elementary Schools; Preschool Education; Secondary Schools; Annotated Bibliographies; Bibliographies; Doctoral Dissertations; Reading Research